2000
DOI: 10.1007/s004250000412
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid and hydraulic conductivity of maize roots: a study using cell- and root-pressure probes

Abstract: Using root- and cell-pressure probes, the effects of the stress hormone abscisic acid (ABA) on the water-transport properties of maize roots (Zea mays L.) were examined in order to work out dose and time responses for root hydraulic conductivity. Abscisic acid applied at concentrations of 100-1,000 nM increased the hydraulic conductivity of excised maize roots both at the organ (root Lp(r): factor of 3 4) and the root cell level (cell Lp: factor of 7-27). Effects on the root cortical cells were more pronounced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
180
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(193 citation statements)
references
References 38 publications
(61 reference statements)
10
180
3
Order By: Relevance
“…Abscisic acid (ABA) accumulation in stressed plants was found to be protective against drought damage, causing stomata closure that reduces water loss via transpiration [13,14], and increasing hydraulic conductance, promoting water movement from roots to leaves [15,16]. In addition, ABA plays an important role in mediating the gene expression in response to water deficit [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Abscisic acid (ABA) accumulation in stressed plants was found to be protective against drought damage, causing stomata closure that reduces water loss via transpiration [13,14], and increasing hydraulic conductance, promoting water movement from roots to leaves [15,16]. In addition, ABA plays an important role in mediating the gene expression in response to water deficit [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The L p of root cortex cells was maximally stimulated ≥30-fold after a 1 h exposure to 1 M ABA, but these effects disappeared over the next hour. In the same studies it was also noted that in contrast to ABA, auxin (IAA) and cytokinin (kinetin) reduced the cell L p by three-to four-fold [98]. Studies at the cell level provide more direct evidence for cell membranes and aquaporins being involved in stimulus-induced regulation of root L p [1-3,5,7,108].…”
Section: Relationships Between Plant Aquaporins and Hormonesmentioning
confidence: 98%
“…Both energy-input and tension-gating mechanisms might be used by the plant to sense changes in turgor pressure and surrounding water availability, and to adapt the membrane water permeability in an ABAdependent manner [75]. In many species including sunflower, barley, sorghum and maize [96][97][98], exogenous ABA enhanced root L p . Short-term effects (i.e.…”
Section: Relationships Between Plant Aquaporins and Hormonesmentioning
confidence: 99%
“…11 It is well known that osmotic stress-derived ABA can reduce leaf hydraulic conductivity and shoot growth, thus reducing the transpiration rate in Arabidopsis leaves, [12][13][14] whereas it can maintain root water uptake by enhancing root growth and root hydraulic conductivity. 8,11,[15][16][17] Recently it is found that the single PYL8 ABA receptor play a key role in mediating ABA-controlled root growth and root response to moisture gradient, means hydrotropism, [17][18] while there is a obvious redundant characteristics of PYR1/PYL/RCAR ABA receptor family in stomatal aperture regulation. 9 A naphthalene sulfonamide ABA agonist pyrabactin, which activates seed ABA responses but fails to trigger substantial responses in vegetative tissues in Arabidopsis thaliana.…”
mentioning
confidence: 99%
“…21 While PYL8 mediates the ability of ABA to inhibit primary root growth through the PP2C-SnRK2 pathway, 18 it together with PYL9 promotes lateral root growth recovery from inhibition independently of the core signaling pathway by enhancing MYB77-dependent transcription of auxin-responsive genes. 17,23 The cell-specificities of PYR1/PYL/RCAR ABA receptors It has been shown that application ABA directly enhance plasma membrane water permeability of roots cortical cells 15 and guard cells, 24 while inhibit that of vascular bundle-sheath cells 12 and has not effect to that of mesophyll cells. 12,24 The core signaling component SnRK2.6 has been documented implicated in plasma membrane intrinsic proteins PIP2;1 activation through protein phosphorylation at Ser-121, thus increase in guard cell permeability to water.…”
mentioning
confidence: 99%